A combination of mobility, load and services for network selection in heterogenous wireless network - Mohd Zaini, Khuzairi; Mohd Shariff, Azizul Rahman; M. Madi, Mohammed Kamal (2015)
WLAN has been considered as a compliment technology for cellular network in the heterogeneous wireless network. Thus, seamless connection between these technologies play important role as the performance indicator. In this paper, we consider the user's velocity and channel holding time to predict the user's dwelling time in the WLAN area to assist in the initial network selection. Based on the mobility prediction, network load and type of services, the proposed algorithm will select the most suitable radio access network for the user. In addition, we also incorporate the traffic offloading method in order to accept as many users to the system while maintaining the quality of service of the users. Through extensive discrete-event simulation, the results show that the proposed solution has better performance as compared to the location-based (WLAN First) and mobility threshold proposals.